Development of Coliphage T5: Ultrastructural and Biochemical Studies - Zweig, Martin (1972)
Electron microscopic studies of Escherichia coli infected with bacteriophage T5(+) have revealed that host nuclear material disappeared before 9 min after infection. This disappearance seemed to correspond to the breakdown of host deoxyribonucleic acid (DNA) into acid-soluble fragments. Little or no host DNA thymidine was reincorporated into phage DNA, except in the presence of 5-fluorodeoxyuridine (FUdR). Progeny virus particles were observed in the cytoplasm 20 min postinfection. Most of these particles were in the form of hexagonal-shaped heads or capsids, which were filled with electron-dense material (presumably T5 DNA). A small percentage (3 to 4%) of the phage heads appeared empty. On rare occasions, crystalline arrays of empty heads were observed. Nalidixic acid, hydroxyurea, and FUdR substantially inhibited replication of T5 DNA. However, these agents did not prevent virus-induced degradation of E. coli DNA. Most of the phage-specified structures seen in T5(+)-infected cells treated with FUdR or with nalidixic were in the form of empty capsids. Infected cells treated with hydroxyurea did not contain empty capsids. When E. coli F was infected with the DO mutant T5 amH18a (restrictive conditions), there was a small amount of DNA synthesis. Such cells contained only empty capsids, but their numbers were few in comparison to those in cells infected under permissive conditions or infected with T5(+). The cells also failed to lyse. These results confirm other reports which suggest that DNA replication is not required for the synthesis of late proteins. The data also indicate that DNA replication influences the quantity of viral structures being produced.